Single Step Synthesis of Porous NiCoO2 for Effective Electrooxidation of Glycerol in Alkaline Medium. Issue 15 (1st January 2018) - Ashok, Anchu; Kumar, Anand; Ponraj, Janarthanan; Mansour, Said A.; Tarlochan, Faris
Abstract : Herein, we report the electrooxidation of glycerol in alkaline media in presence of highly active and durable NiCoO2 catalyst synthesized using single step solution combustion synthesis (SCS) and compare its activity with NiO and Co3 O4 prepared using the same method. X-ray diffraction (XRD), X-Ray Photoelectron Spectroscopy (XPS), Scanning electron microscopy (SEM) with EDS and Transmission electron microscopy (TEM) along with EDS elemental/phase mapping were used to analyze the crystallinity, morphology and phase composition of the synthesized particles. TEM image with phase mapping confirms the existence of mixed NiCoO2 and these materials shows enhanced performance when compared with individual metal oxides. The onset potential of NiCoO2 is much lower and the oxidation current density obtained is relatively higher. More importantly, the current density and stability of NiCoO2 obtained from chronoamperometry makes it a promising catalyst for glycerol based fuel cells.